2013
DOI: 10.1210/en.2013-1331
|View full text |Cite
|
Sign up to set email alerts
|

Kisspeptin, Neurokinin B, and Dynorphin Act in the Arcuate Nucleus to Control Activity of the GnRH Pulse Generator in Ewes

Abstract: Recent work has led to the hypothesis that kisspeptin/neurokinin B/dynorphin (KNDy) neurons in the arcuate nucleus play a key role in GnRH pulse generation, with kisspeptin driving GnRH release and neurokinin B (NKB) and dynorphin acting as start and stop signals, respectively. In this study, we tested this hypothesis by determining the actions, if any, of four neurotransmitters found in KNDy neurons (kisspeptin, NKB, dynorphin, and glutamate) on episodic LH secretion using local administration of agonists and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
151
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 205 publications
(165 citation statements)
references
References 67 publications
13
151
0
1
Order By: Relevance
“…Here we extend these findings by demonstrating in OVX ewe that the diminution of plasma LH levels is specifically due to an interruption of the LH pulse. The prolongation of the LH pulse interval observed here in response to iv treatment with an NK3R antagonist is consistent with previous observations made in ewe after the infusion of NK3R antagonists directly into the brain (17,27). The restoration of the LH pulse in the current study is coincident with the decline of ESN364 plasma levels below approximately 1.5 M, data that are generally consistent with the PK-PD relationships previously established for ESN364 in monkeys (11).…”
Section: Discussionsupporting
confidence: 92%
“…Here we extend these findings by demonstrating in OVX ewe that the diminution of plasma LH levels is specifically due to an interruption of the LH pulse. The prolongation of the LH pulse interval observed here in response to iv treatment with an NK3R antagonist is consistent with previous observations made in ewe after the infusion of NK3R antagonists directly into the brain (17,27). The restoration of the LH pulse in the current study is coincident with the decline of ESN364 plasma levels below approximately 1.5 M, data that are generally consistent with the PK-PD relationships previously established for ESN364 in monkeys (11).…”
Section: Discussionsupporting
confidence: 92%
“…Importantly, increases in extracellular kisspeptin levels within the region of the ARN can correlate with pulsatile GnRH secretion (48) and injection of Gpr54 antagonists into the ARN region decreases LH pulse frequency (49,50). The location of Gpr54 antagonism within those studies is unknown and may possibly be at the level of the Gpr54-expressing GnRH neuron dendron/terminals within and adjacent to the ARN, where they would suppress the putative episodic kisspeptin drive to GnRH secretion.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this notion, Luque et al (2007) noted a defective expression of Kiss1 in Npyknockout mice and suggested that a normal NPY neuronal network is essential for KP-containing neurons to function accurately. Similarly, dynorpin A and neurokinin B coexpressions have been identified on KPergic neurons (Goodman et al 2013). It will be interesting to know whether KP and GnIH neurons contain receptors for AgRP, NPY, GALP, CART, and POMC or receive afferent projections from these neuronal networks of the feeding and satiety center.…”
Section: Role Of Kp In Regulation Of Reproductionmentioning
confidence: 93%